Foreign Investment and Its Legal Impact on Local Resources and the Environment in Tourist Destinations - Islam, Rudi; Fikri, Abdillah (Justicia Insight, 2025)
Foreign investment plays a crucial role in the economic growth of tourist destinations by stimulating infrastructure development, generating employment, and promoting regional competitiveness. However, the influx of foreign capital often raises complex legal issues related to the management of local resources and environmental sustainability. This article examines the legal implications of foreign investment on natural resource utilization and environmental protection within tourist areas. Using a normative legal research approach supported by case studies in selected tourist destinations, the study highlights how legal frameworks regulate foreign investors’ activities, particularly concerning land use, water management, and waste disposal. Findings indicate that while foreign investment contributes to economic advancement, weak enforcement of environmental regulations and lack of community involvement often lead to overexploitation of resources and ecological degradation. The study suggests strengthening environmental law enforcement, enhancing local community participation, and harmonizing investment regulations with sustainable development principles. This research provides valuable insights for policymakers in balancing the dual objectives of economic growth and environmental protection in tourism-based regions.